Strengthening of structural steel st3 by high-speed friction method in the technological environment of carbon - Kapral, Yu.P.; Ozymok, Yu.I.; Burdyak, M.R.; Palyuh, B.I. (Forestry, Forest, Paper and Woodworking Industry, 2019)
Effectiveness researches of strengthening of structural steel St3 by high-speed friction method in the technological environment of carbon have been conducted. The billets of round chopping made of St3 steel were strengthened by the method of high-speed friction at the variable mode factors: the feed speed of the billets and the pressing force of the disk to the billet. The researches were conducted in the technological environment of carbon and air. Physico-mechanical characteristics of the obtained layers were measured after strengthening. According to the results of the research the microhardness of the layer at depths up to 150μm was found to be significantly higher in the the technological environment of carbon than in the environment of air on all modes. At the further distance from the upside microhardness is approximately the same during strengthening in both modes. Such increase in microhardness can be explained by the fact that the upside layers of the metal are melted and saturated with carbon because of the significant heat release from friction. Steel microhardness increases due to the tempering while carbon concentration increases in steel. At the depth 50μm from the upside due to the strengthening in the technological environment of carbon microhardness increases by 13…25% depending on strengthening modes. In case of strengthening in the technological environment of air the microhardness of upside layers (up to 150 μm) is lower than maximum microhardness. Comparing the results of different modes strengthening was found that the highest physico-mechanical indicators of strengthened layer on the steel St3 billets can be obtained under the following strengthening modes: pressing force of the disk to the billet – 800H; the feed speed of the billets – 0,5 m/min. Maximum microhardness is about 8,5 GPa at the depth of 200μm during such strengthening modes. Microhardness is about 8 GPa at the depth of 200…550μm and is begining to decrease till starting microhardness at the depth of 550μm to 850μm. The billets in the form of a tube made of St3 steel are used for production of band-sawing machine directors. Comparing the obtained results and the results of the activity [1] it is proved that for the production of band-saw machine directors it is efficient to use full-bodied tubes because the side thickness of the hollow tube is not sufficient for heat dissipation and effective use of the self-hardening effect.